Abnormal phosphorylation of human LRH1 at Ser510 predicts poor prognosis and promotes cell viability in lung squamous cell carcinoma - Hayato Mine; Kotaro Sugimoto; Makoto Kobayashi; Hironori Takagi; Naoyuki Okabe; Satoshi Muto; Yasuyuki Kobayashi; Yuko Hashimoto; Hiroyuki Suzuki; Hideki Chiba (BMC Cancer)
Abstract The nuclear receptor liver receptor homolog 1 (LRH1)/NR5A2 is aberrantly expressed in diverse cancer types, including liver and lung cancers. Since we previously showed that excessive phosphorylation of human LRH1 at S510 (hLRH1pS510-high) is predictable of hepatocellular carcinoma recurrence, we here clarified the clinicopathological and biological significance of hLRH1pS510-high in lung cancer. By immunohistochemistry using an anti-hLRH1pS510 monoclonal antibody, we evaluated the hLRH1pS510 signals in 151 and 150 cases of lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) tissues, respectively, and performed clinicopathological analysis. hLRH1pS510 was localized in the nucleus of tumor cells in LUAD and LUSC tissues with different intensity and proportions among the patients. Of note, the strong hLRH1pS510 signal was occasionally detectable in LUAD and LUSC cells at the expanding tumor edges. A semi-quantitative analysis revealed that 28 (18.4%) and 36 (24.0%) of LUAD and LUSC cases, respectively, exhibited hLRH1pS510-high. Kaplan-Meier plots showed significant differences in the disease-free survival (DFS) between the hLRH1pS510-high and hLRH1pS510-low groups in LUSC, but not in LUAD patients. hLRH1pS510-high was also significantly correlated with recurrence in LUSC patients. Additionally, by multivariate analysis, hLRH1pS510-high represented an independent biomarker for the DFS of LUSC patients. Furthermore, the impact of hLRH1pS510 on the viability of LUSC cells was evaluated by comparing phenotypes among two distinct LUSC cell lines expressing wild-type LRH1, LRH1S510A, and LRH1S510E. Consequently, we demonstrated that phosphorylation of hLRH1S510 accelerates the viability of LUSC cells. Thus, hLRH1pS510 is attractive not only as the predictive biomarker for LUSC but also as the potential therapeutic target.